2022
DOI: 10.1021/acs.accounts.2c00038
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lived Organic Room-Temperature Phosphorescence from Amorphous Polymer Systems

Abstract: Metrics & MoreArticle Recommendations * sı Supporting Information CONSPECTUS: Long-lived organic room-temperature phosphorescence (RTP) materials have recently drawn extensive attention because of their promising applications in information security, biological imaging, optoelectronic devices, and intelligent sensors.In contrast to conventional fluorescence, the RTP phenomenon originates from the slow radiative transition of triplet excitons. Thus, enhancing the intersystem crossing (ISC) rate from the lowest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
166
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 269 publications
(167 citation statements)
references
References 53 publications
0
166
0
1
Order By: Relevance
“…[8][9][10] In general, RTP is difficult to achieve at room temperature due to the spin prohibition of triplet exciton transitions and the fact that triplet excitons are easily quenched by oxygen and other nonradiative processes. [11][12][13] Researchers would achieve RTP by the following methods: (1) doping rare earth metal ions or heteroatoms into the phosphors to facilitate intersystem crossing (ISC) processes; (2) embedding phosphors into rigid substrates, such as polymers, ionic crystals, amorphous materials, and macrocyclic molecules to suppress vibration and rotation; and (3) selecting rigid precursors and using self-assembly to regulate molecular stacking patterns, restricting nonradiative processes and protecting triplet excitons. [14][15][16][17] Over the past decade, researchers have made a steady stream of breakthroughs in the preparation of RTP materials, targeting mainly inorganic complexes or metal-free organic compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] In general, RTP is difficult to achieve at room temperature due to the spin prohibition of triplet exciton transitions and the fact that triplet excitons are easily quenched by oxygen and other nonradiative processes. [11][12][13] Researchers would achieve RTP by the following methods: (1) doping rare earth metal ions or heteroatoms into the phosphors to facilitate intersystem crossing (ISC) processes; (2) embedding phosphors into rigid substrates, such as polymers, ionic crystals, amorphous materials, and macrocyclic molecules to suppress vibration and rotation; and (3) selecting rigid precursors and using self-assembly to regulate molecular stacking patterns, restricting nonradiative processes and protecting triplet excitons. [14][15][16][17] Over the past decade, researchers have made a steady stream of breakthroughs in the preparation of RTP materials, targeting mainly inorganic complexes or metal-free organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Although inorganic RTP materials with prolonged light emission are actively being sought for many applications including optoelectronic devices, photocatalysis, and emergency signage, 4–7 they are less suitable for applications such as anticounterfeiting and bioimaging materials, where bright, subsecond afterglow is required 8–10 . In general, RTP is difficult to achieve at room temperature due to the spin prohibition of triplet exciton transitions and the fact that triplet excitons are easily quenched by oxygen and other nonradiative processes 11–13 . Researchers would achieve RTP by the following methods: (1) doping rare earth metal ions or heteroatoms into the phosphors to facilitate intersystem crossing (ISC) processes; (2) embedding phosphors into rigid substrates, such as polymers, ionic crystals, amorphous materials, and macrocyclic molecules to suppress vibration and rotation; and (3) selecting rigid precursors and using self‐assembly to regulate molecular stacking patterns, restricting nonradiative processes and protecting triplet excitons 14–17 .…”
Section: Introductionmentioning
confidence: 99%
“…21 However, CIP efficiency is highly dependent on the morphology of the material, requiring high crystal quality (for small molecules) 22,23 or large molecular weight (for polymers). 24,25 Therefore, it is difficult to realize the CIP of amorphous nanomaterials which have huge application potential in biological imaging, optoelectronic devices, and information storage. It is necessary to develop a simple method to obtain nanomaterials with long lifetime CIP.…”
Section: Introductionmentioning
confidence: 99%
“…Room temperature phosphorescence (RTP) in organic materials has aroused great attention owing to their potential applications in sensing, bioimaging, X-ray scintillators, etc. [1][2][3][4][5][6][7] There are two inevitable obstacles to obtaining the RTP of organic compounds: one is the scarce population of triplet excitons caused by the spin-forbidden intersystem crossing (ISC) from singlet to triplet excited states, and the other is the ultrafast nonradiative deactivation of triplet excitons under ambient conditions. Normally, introducing n-electron groups into p-conjugated chromophores is favourable for accelerating the ISC process, 8,9 and rigid environments are beneficial to stabilize the triplet excitons by restricting molecular motions through multiple intermolecular interactions; the combination of these two strategies can trigger efficient organic RTP.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26] Recently, the electron-donating groups (EDGs) have been demonstrated to weaken the intermolecular interaction among the adjacent p-units, which is harmful for the stabilization of triplet excitons, thereby reducing the RTP performance. [16][17][18] For example, Ehsan et al reported that 4H-benzo [9,1]quinolizino [3,4,5,6,7-defg]acridine-4,8,12-trione (QAT) emits a bright RTP with an efficiency (F p ) of 42.0% in crystals, whereas the tert-butyl fused QAT (QAT-tBu) shows a faint RTP but bright fluorescence with an efficiency (F f ) of 11.0%. 18 In contrast, several studies found that the involvement of EDGs can promote RTP efficiency (F p ) and prolong RTP lifetime (t p ); e.g., the F p was increased from 0.9% in thioxanthone (TX) to 11.7% in methoxy-substituted TX (TX-OMe); 22,23 the t p was prolonged from 0.02 ms in N-methyl phthalimide (MP) to 39.9 ms in norbornyl (NB) fused MP (MP-NB).…”
Section: Introductionmentioning
confidence: 99%